Method development and validation for omega-3 fatty acids DHA and EPA in fish using gas chromatography with flame ionization detection GC-FID - Muhammad Alinafiah, Suryati; Azlan, Azrina; Ismail, Amin; Mahmud Ab Rashid, Nor Khaizura (MDPI AG, 2021)
Gas chromatography with flame ionization detection (GC-FID) has often been used to quantify fatty acids in fish. This study validated the common method for determining omega-3 fatty acids (DHA and EPA) in the raw and cooked warm-water fish, selayang, using GC-FID for subsequent evaluation on EPA and DHA retention using the Weibull model. The EPA and DHA were separated using a high-polarity capillary GC HP-88 column (60 m length, 0.25 mm ID, 0.2 μm DF) with a total run time of 45.87 min. The method was validated in linearity, precision, accuracy, specificity and sensitivity based on ICH requirements. In addition, it was found that the method had a high recovery rate (>95%) and good precision (RSD ≤ 2%) with overall RSDs ranging below 0.001% for both omega-3 PUFA. In conclusion, this method identified and quantified fatty acids and omega-3 accurately and precisely and can be used effectively for routine FAME analysis in fish samples.